Ethosomes: A Novel Approach to Overcoming Skin Barriers for Efficient Drug Delivery - Kapoor, Anupriya (Asian Journal of Pharmaceutics (AJP), 2025)
Ethosomes represent an advancement in transdermal drug delivery systems, offering enhanced skin penetration and drug delivery capabilities. This review explores the composition, structure, preparation methods, and evaluation techniques of ethosomes, highlighting their benefits and mechanisms of action. Ethosomes, comprised of phospholipids, ethanol, and water, disrupt the stratum corneum’s lipid structure, facilitating drug permeation. Various preparation methods, including cold, hot, mechanical dispersion, and thin-film hydration techniques, are discussed. Evaluation methods such as transmission electron microscopy, scanning electron microscopy, and dynamic light scattering are crucial for characterizing ethosome properties. The mechanism of ethosome-mediated skin penetration involves interaction with stratum corneum lipids, vesicle flexibility, and fusion with skin lipids, enabling efficient drug release. Ethosomes offer versatility in delivering both hydrophilic and lipophilic drugs, with applications in treating various conditions. Their biocompatibility, safety, and advantages over other delivery systems make them a promising choice for improved transdermal drug delivery